Thermodynamic and Exergoeconomic Study of an Absorption-Compression Refrigeration Cycle Driven by a Geothermal Energy Resource - Armin Khazaei Nam; Asgar Minaei; Mohammad Ebadollahi; Hadi Ghaebi (مجله مدل سازی در مهندسی)
In recent years, a growing emphasis has been on providing sustainable energy to reduce carbon emissions and promote energy efficiency. This article aims to investigate thermodynamic and exergoeconomic analyses of the cascade absorption refrigeration with a vapor compression refrigeration system driven by a geothermal renewable energy source. The purpose of this system is to produce four different products: power, heating load, cooling, and fresh water. The effect of temperature and mass flow rate parameters of the geothermal source, fresh air ratio parameter, condenser temperature, evaporator-condenser outlet temperature of the absorption refrigeration section, and the evaporator temperature of the vapor compression refrigeration system on the essential decision variables of the system and also on the temperature provided for the thermal comfort of the house and The flow of fresh water produced by the fan coil unit is provided, which has the most influence on the decision parameters, is caused by the output temperature and mass flow rate of the geothermal energy source. The system output parameters such as COP, W ̇_net, η_energy, η_exergy and SUCP in the basic mode are equal to 0/35, 9/78kW, 73/5%, 32/25%, and 101/11$/GJ respectively. The highest exergy destruction occurs in the geothermal reinjection, with an amount of 53% of the total exergy destruction. The calculations performed in this research were done in the EES software.